2003
DOI: 10.2134/agronj2003.0160
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Iron Deficiency in Corn with Seed Row–Applied Iron Sulfate

Abstract: Fe deficiency is foliar application of Fe solutions. This method of correction usually alleviates chlorosis; how-Corn (Zea mays L.) grown on calcareous, high-pH soils is susceptiever, the results from a foliar application may be only ble to Fe deficiency, which can reduce grain yield by as much as 20%.temporary and actually depress the plant's Fe stress mech-The objective of this study was to evaluate several treatments of FeSO 4 anisms by preventing the increase in Fe-reducing capacthat could be used with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…Liquid solutions containing low rates of chelated or non-chelated Fe are often used to temporarily correct Fe deficiencies (Anderson, 1982;Godsey et al, 2003;Goos and Johnson, 2000;Mengel, 1995;Pestana et al, 2001;Randall, 1981;Reed et al, 1988;Zaiter et al, 1992). If these materials are applied in a fashion that results in adherence to leaf surfaces, the Fe is absorbed for use by the plant (Mengel, 1995).…”
Section: Foliar Spraysmentioning
confidence: 99%
“…Liquid solutions containing low rates of chelated or non-chelated Fe are often used to temporarily correct Fe deficiencies (Anderson, 1982;Godsey et al, 2003;Goos and Johnson, 2000;Mengel, 1995;Pestana et al, 2001;Randall, 1981;Reed et al, 1988;Zaiter et al, 1992). If these materials are applied in a fashion that results in adherence to leaf surfaces, the Fe is absorbed for use by the plant (Mengel, 1995).…”
Section: Foliar Spraysmentioning
confidence: 99%
“…Fe deficiency can reduce maize grain yield by as much as 20% (Godsey et al, 2003). Correcting Fe deficiency through soil amendments and foliar sprays of Fe has been partially successful considering the fact that low availability rather than low total amount usually limits Fe uptake by plant roots.…”
Section: Introductionmentioning
confidence: 99%
“…The most effective stable iron chelate, FeEDDHA (ferric ethylenediamine di(o-hydroxyphenylacetate) currently costs about $69 ha -1 for a single soil or foliar treatment to provide 4.5 kg Fe ha -1 . Godsey et al (2003) observed that FeSO 4 . 7H 2 O seed row application increased maize yield on soil with a high pH.…”
Section: Introductionmentioning
confidence: 99%
“…Soil composition, environmental factors, and plant iron deficiency response mechanisms influence the incidence of iron chlorosis. However, the key underlying cause of iron deficiency on calcareous soil is limited iron uptake and subsequent translocation and utilization within plants because of the high bicarbonate ion concentration in the soil (Godsey et al 2003;Mengel 1994). The primary effects of bicarbonate are the neutralization of the H + ion in the rhizosphere, the reduction of plasma membrane activity of roots and an increase in root internal pH (Loeppert et al 1994).…”
Section: Introductionmentioning
confidence: 99%